ESL students’ perspectives in understanding English reading materials: the insight from a language classroom / Norizul Azida Darus, Norhajawati Abdul Halim and Aini Akmar Mohd Kasim - Darus, Norizul Azida; Abdul Halim, Norhajawati; Mohd Kasim, Aini Akmar (Universiti Teknologi MARA, Perlis, 2019)
Reading is an active language activity which comprises a variety of skills. The reading comprehension lessons are normally used by instructors to help students develop their reading skills. However, in most cases, it was found that reading comprehension lessons have been centered on passages or texts followed by a set of questions. These questions were usually designed to merely test the students’ comprehension of the given text and not part of the teaching process. It has been seen and said that students merely scan for information in the text to answer these questions but were unable to relate to it. This could be due to cultural factors including the lack of reading habits among the students but most likely due to the manner reading has been taught. Thus, this study aims to investigate the teaching of English Reading materials and reading comprehension to a group of 15 students undergoing Diploma courses in UiTM Perlis. This is a qualitative study and the data are gathered through classroom observations, students’ journals, instructor’s diary and interview sessions with the students and instructor to get clearer picture on the problems they face when having to comprehend English materials. The insight generated by the description and analysis of the data collected for this study can be used for a variety of purposes, particularly; to better understand the problems faced by students when having to read in a second language, to help ESL curriculum and instructional practices, and to provide useful insights for educational language policy making.